If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x+(4x-3)=60-(4x+3)
We move all terms to the left:
12x+(4x-3)-(60-(4x+3))=0
We get rid of parentheses
12x+4x-(60-(4x+3))-3=0
We calculate terms in parentheses: -(60-(4x+3)), so:We add all the numbers together, and all the variables
60-(4x+3)
determiningTheFunctionDomain -(4x+3)+60
We get rid of parentheses
-4x-3+60
We add all the numbers together, and all the variables
-4x+57
Back to the equation:
-(-4x+57)
16x-(-4x+57)-3=0
We get rid of parentheses
16x+4x-57-3=0
We add all the numbers together, and all the variables
20x-60=0
We move all terms containing x to the left, all other terms to the right
20x=60
x=60/20
x=3
| 2(12x-6)=36 | | 2(3+4x)=6-4x | | -3+4x=61 | | 2p^2-20p=50 | | 60/4= | | 29-x=2x-1 | | 10x+25=4x | | 32p^2+50=0 | | 2^x+9×2^x=40 | | 4x-30+6x-30+3x+x=360 | | 3x+3=37 | | X+7/3=1+3x-2/5 | | 2y+5y-7y=0 | | 3(2x-50)=735 | | 5x+3=3x–5 | | 5.5x-14.3=7.7 | | 3x-3=2x7x | | 3r-2=5r+7 | | 1.5t^2-36t=0 | | (X)=2x-3x+7 | | 3.14159(d/2)^(2)=0 | | A=3.14159(d/2)^(2) | | P+q=0 | | 2x-12÷3=-7 | | 9d/2-4/2=1 | | 3(9/6)-y=0 | | 3x-5+55+x+20=180 | | 4(2-3x)=-10-3x | | 8x+5x-57=36-6x | | 9d-4/2=1 | | x-80=150 | | 14x^2+64x+45=0 |